Soil micromorphology in archaeology: history, objectives, possibilities and prospects - M. A. Bronnikova; A. V. Panin; V. V. Murasheva; A. A. Golyeva (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
The history of applying soil micromorphology in archaeology in Russia and abroad is overviewed. The main objectives of soil micromorphological analysis of archaeological objects are specified. The possibilities offered by this method are illustrated by the example of a micromorphological study of a cultural layer of an Early Medieval settlement. The prospects of archaeological soil micromorphology development are outlined.